Effect of integrated nutrient management practices on productivity of blackgram (Vigna mungo) - BEHERA, PRATISHRUTI; MOHAPATRA, ASHOK (The Indian Journal of Agricultural Sciences, 2022)
A field study was carried out at Chatabara village, Institute of Agricultural Sciences (IAS), Siksha “O” Anusandhan Deemed to be University, Bhubaneswar, Odisha during winter (rabi) season of 2019–20 to evaluate the effect of different INM practices on productivity, profitability and nutrient acquisition by blackgram. Results showed that INM with 100% RDF+ FYM (5 t/ha) + Nutri-priming with Mo and P (Ammonium molybdate 0.1% and 1% P solution of SSP) can be the best practice for the cultivation of blackgram under winter (rabi) season with an yield level of 741 kg/ha and net returns of 39.2 × 103 `/ha. However, for farmers convenience point of view, INM with RDF+5.0 t/ha of FYM can be the 2nd best practice for the cultivation of blackgram with an yield level of 687 kg/ha and net returns of 35.2 × 103 `/ha.